500 Roles for inflammation in livestock muscle growth and repair. (7th December 2018) - Reed, S
Abstract: Efficient muscle growth in livestock is critical for meat product quantity and quality, as well as animal health and metabolism. Intrinsic and environmental challenges can impair pre-natal muscle development and post-natal muscle growth. The pre-natal environment, including maternal nutrition, heat stress and disease, as well as these and other factors in the post-natal environment can all increase pro-inflammatory mediators in livestock. Changes in the balance of pro- and anti-inflammatory status during muscle development and/or post-natal growth can negatively impact myoblast proliferation, muscle fiber formation, and hypertrophy. This results in reduced muscle mass and may partition nutrients to other tissues, such as adipose and connective tissue. Further, inflammation has been linked with changes in cellular metabolism, resulting in increased energy expenditure and decreased efficiency. Together, these alter muscle composition, and have the potential to negatively impact meat quality. Understanding the impacts of inflammation on myoblast proliferation and differentiation, muscle fiber hypertrophy, and muscle metabolism will allow for improved management techniques and therapeutic interventions, thus improving health and production outcomes in livestock.